Baccatin derivatives and a process for producing the same - MANDAI, TADAKATSU; HARA, KOJI; MIKUNI, KATSUHIKO; NAKANISHI, KATSUYOSHI; HARA, KOZO; OKUMOTO, HIROSHI (2000)
The object of the invention is to develop baccatin derivatives useful for preparing taxoid compounds such as paclitaxel and a process for the producing the same. The invention provides baccatin derivatives represented by the general formula (I) as well as a process for producing baccatin derivatives represented by the general formula (I) above, which comprises allowing a baccatin represented by the general formula (II) to react with a beta -ketoester in the absence of a catalyst or in the presence of a tin compound or an amine base, preferably under reduced pressure.